Gold-loaded photocatalyst, photocatalyst peculiar smell removal spray and preparation method and application of photocatalyst peculiar smell removal spray

Through gold-loaded photocatalyst catalysts, it can effectively remove odors from artificial leather under visible light, solving the problem that existing photocatalyst materials can effectively antibacterial under ultraviolet conditions but cannot remove odors from artificial leather, and achieve efficient removal of odors under visible light conditions .

CN119425678AInactive Publication Date: 2025-02-14ZHEJIANG MEISHENG NEW MATERIALS CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202510026476.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Artificial leather will produce odor during use. The existing photocatalyst materials can effectively antibacterial under ultraviolet conditions, but they cannot effectively remove odors in artificial leather.

Method used

Using a gold-supported photocatalyst catalyst, ultrasonic mixing ultrafine titanium dioxide powder and water, adding tetrachloroauric acid trihydrate and sacrificial agent, photodeposition and freeze-drying, photocatalyst deodorization spray with excellent odor removal performance was prepared.

Benefits of technology

The gold-loaded photocatalyst catalyst has high odor removal performance in the visible light range, which can effectively reduce the odor of artificial leather, and is simple in preparation, non-toxic and no secondary pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425678A_ABST
    Figure CN119425678A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of peculiar smell removal materials, and provides a gold-loaded photocatalyst, a photocatalyst peculiar smell removal spray and a preparation method and application of the photocatalyst peculiar smell removal spray. The method comprises the following steps: performing ultrasonic mixing on superfine titanium dioxide powder and water to obtain a titanium dioxide solution; the preparation method comprises the following steps: mixing a titanium dioxide solution, tetrachloroauric acid trihydrate and a sacrificial agent, and sequentially carrying out photodeposition and freeze drying to obtain the gold-loaded photocatalyst. A tetrachloroauric acid trihydrate is loaded on the surface of superfine titanium dioxide powder in a photodeposition manner under the action of a sacrificial agent to obtain a gold-loaded photocatalyst; the high-activity clusters and monatomic gold not only retain various properties of the titanium dioxide photocatalyst, but also expand the absorption range of visible light and improve the light response range of the catalyst, and the catalytic activity is further improved by the heat effect generated by surface plasmas, so that the purpose of removing peculiar smell is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of deodorizing materials, and in particular to a gold-loaded photocatalyst and a photocatalyst deodorizing spray, as well as a preparation method and application thereof. Background Art

[0002] Artificial leather (also known as synthetic leather or faux leather) is widely used in automotive interiors due to its excellent durability, cost advantages and environmental properties. Compared with genuine leather, artificial leather not only meets visual and tactile needs, but also has higher stain resistance and easy maintenance. However, due to the solvent residue in the production process and the odor problem of artificial materials, it will produce a certain odor during use. The odor of artificial leather mainly comes from the chemicals used in its manufacturing process, which include organic solvents, plasticizers, additives and dyes. These substances will release volatile organic compounds (VOCs) in a closed and hot environment, which will have a serious impact on people's physical and mental health. Therefore, how to effectively remove these odors is the key to limiting the large-scale application of artificial leather.

[0003] Photocatalytic deodorization is a technology that uses the catalytic effect of photocatalyst materials under light to achieve the purpose of deodorization. Photocatalyst materials can produce redox reactions under the irradiation of ultraviolet or visible light, generating hydroxyl free radicals and superoxide anions with strong oxidizing properties. These active oxygen species can effectively decompose VOCs and other odor-producing gases. Ordinary photocatalyst materials need to be under ultraviolet conditions to have good antibacterial properties and cannot effectively remove odors from artificial leather.

[0004] Therefore, it is of great significance to study and obtain a photocatalyst deodorizing spray that improves the light response range and catalytic activity. Summary of the invention

[0005] The purpose of the present invention is to provide a gold-loaded photocatalyst catalyst and a photocatalyst deodorizing spray and a preparation method and application thereof in order to overcome the deficiencies of the prior art. The photocatalyst deodorizing spray has excellent deodorizing performance in the visible light range and can be used in microfiber artificial leather.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a method for preparing a gold-supported photocatalyst, comprising the following steps: 1) Ultrasonic mixing of ultrafine titanium dioxide powder and water to obtain a titanium dioxide solution; 2) Mixing titanium dioxide solution, tetrachloroauric acid trihydrate and a sacrificial agent, sequentially performing photodeposition and freeze drying to obtain a gold-loaded photocatalyst.

[0007] Preferably, in step 1), the mass volume ratio of the ultrafine titanium dioxide powder to water is 10-100 mg:100 mL.

[0008] Preferably, the mass ratio of the tetrachloroauric acid trihydrate in step 2) to the ultrafine titanium dioxide powder in step 1) is 1-5:100.

[0009] Preferably, the sacrificial agent in step 2) comprises methanol, ethanol, triethanolamine or ethylenediamine; the volume mass ratio of the sacrificial agent to the ultrafine titanium dioxide powder in step 1) is 0.5-0.75 mL:1 mg.

[0010] Preferably, in step 2), the temperature of the photodeposition is 20-30° C., the time of the photodeposition is 3-6 hours, and the wavelength of the light source used for the photodeposition is 350-380 nm, and the power is 0.8 mW-310 W.

[0011] The present invention also provides a gold-loaded photocatalyst prepared by the method for preparing the gold-loaded photocatalyst.

[0012] The present invention also provides a method for preparing a photocatalyst deodorizing spray using the gold-loaded photocatalyst, comprising the following steps: The gold-loaded photocatalyst is dissolved in an ethanol solution to obtain a photocatalyst deodorizing spray.

[0013] Preferably, in the ethanol solution, the volume ratio of anhydrous ethanol to water is 1-9:1-9; and the mass volume ratio of the gold-supported photocatalyst to the ethanol solution is 10-100 mg:500 mL.

[0014] The present invention also provides a photocatalyst deodorizing spray prepared by the method for preparing the photocatalyst deodorizing spray using the gold-loaded photocatalyst.

[0015] The invention also provides application of the photocatalyst deodorizing spray in deodorizing superfine fiber artificial leather.

[0016] The beneficial effects of the present invention include the following: 1) The present invention adopts simple photodeposition to prepare a gold-loaded ultrafine titanium dioxide powder photocatalyst. Tetrachloroauric acid trihydrate is loaded on the surface of the ultrafine titanium dioxide powder by photodeposition under the action of a sacrificial agent to obtain a gold-loaded photocatalyst (P25-Au). The highly active clusters and single atomic gold not only retain the various properties of the titanium dioxide photocatalyst, but also expand the absorption range of visible light and improve the light response range of the catalyst. The thermal effect generated by the surface plasma further improves the catalytic activity, thereby achieving the purpose of removing odor.

[0017] 2) The preparation method of the gold-loaded photocatalyst of the present invention is simple, non-toxic, and has no secondary pollution. The light absorption range of the gold-loaded photocatalyst is within the visible light range, and it has broad application prospects in the field of photocatalytic odor removal.

[0018] 3) The gold-loaded photocatalyst prepared by the present invention has good deodorizing performance in the visible light range and has great potential in the field of artificial leather deodorizing; spraying the photocatalyst deodorizing spray prepared by the present invention on the microfiber artificial leather can enhance the functionality of the product and improve the user experience; products made of microfiber leather sprayed with the photocatalyst deodorizing spray, such as furniture, car interiors, clothing, etc., can provide a more comfortable use experience. Microfiber leather sprayed with the photocatalyst deodorizing spray can better meet the market demand for healthy and environmentally friendly products. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 X-ray diffraction patterns of the gold-supported photocatalyst of Example 1 and the pure P25 ultrafine titanium dioxide powder of Comparative Example 1; Figure 2 The energy spectrum analysis and element mapping results of the gold-loaded photocatalyst of Example 1 and the pure P25 ultrafine titanium dioxide powder of Comparative Example 1, wherein (a) is the energy spectrum analysis, (b) is the O element, (c) is the Ti element, and (d) is the Au element; Figure 3 The UV-visible absorption spectra of the gold-loaded photocatalyst of Example 1 and the pure P25 ultrafine titanium dioxide powder of Comparative Example 1 are shown. DETAILED DESCRIPTION

[0020] The present invention provides a method for preparing a gold-supported photocatalyst, comprising the following steps: 1) Ultrasonic mixing of ultrafine titanium dioxide powder and water to obtain a titanium dioxide solution; 2) Mixing titanium dioxide solution, tetrachloroauric acid trihydrate and a sacrificial agent, sequentially performing photodeposition and freeze drying to obtain a gold-loaded photocatalyst.

[0021] In the present invention, the mass volume ratio of the ultrafine titanium dioxide powder and water in step 1) is preferably 10-100 mg:100 mL, more preferably 20-80 mg:100 mL, and more preferably 30-50 mg:100 mL.

[0022] In the present invention, the ultrafine titanium dioxide powder is preferably P25 ultrafine titanium dioxide powder.

[0023] In the present invention, the mass ratio of the tetrachloroauric acid trihydrate (AuCl3·HCl·3H2O) in step 2) to the ultrafine titanium dioxide powder in step 1) is preferably 1-5:100, more preferably 2-4:100, and even more preferably 3:100.

[0024] In the present invention, tetrachloroauric acid trihydrate is preferably added in the form of an aqueous solution of tetrachloroauric acid trihydrate, wherein the aqueous solution of tetrachloroauric acid trihydrate is tetrachloroauric acid trihydrate dissolved in deionized water; the aqueous solution of tetrachloroauric acid trihydrate, the concentration of tetrachloroauric acid trihydrate is preferably 0.8-1.2 mg / mL, more preferably 0.9-1.1 mg / mL, and more preferably 1 mg / mL.

[0025] In the present invention, the sacrificial agent in step 2) preferably comprises methanol, ethanol, triethanolamine or ethylenediamine; the volume mass ratio of the sacrificial agent to the ultrafine titanium dioxide powder in step 1) is preferably 0.5~0.75mL:1mg, more preferably 0.55~0.7mL:1mg, and more preferably 0.62~0.67mL:1mg.

[0026] In the present invention, the temperature of the photodeposition in step 2) is preferably 20-30°C, more preferably 22-28°C, more preferably 24-25°C, and the time of photodeposition is preferably 3-6h, more preferably 4-5h; the wavelength of the light source used for photodeposition is preferably 350-380nm, more preferably 360-370nm, more preferably 365nm, and the power is preferably 0.8mW-310W.

[0027] In the present invention, when the light source is an LED lamp, the power is preferably 0.8-2 mW, more preferably 1-1.5 mW; when the light source is a xenon lamp, the power is preferably 290-310 W, more preferably 300 W.

[0028] In the present invention, there is no specific requirement for freeze-drying conditions, and the freeze-drying conditions can be adjusted according to the sample yield and other conditions. After the samples are collected, they are stored in a dry place away from light for preparing the photocatalyst spray.

[0029] The present invention also provides a gold-loaded photocatalyst prepared by the method for preparing the gold-loaded photocatalyst.

[0030] The invention also provides a method for preparing a photocatalyst deodorizing spray by using the gold-loaded photocatalyst, and the photocatalyst deodorizing spray is obtained by dissolving the gold-loaded photocatalyst in an ethanol solution.

[0031] In the ethanol solution of the present invention, the volume ratio of anhydrous ethanol to water is preferably 1-9:1-9, more preferably 1-6:1-6, and more preferably 1:4; the mass volume ratio of the gold-supported photocatalyst (P25-Au) to the ethanol solution is preferably 10-100 mg:500 mL, more preferably 20-80 mg:500 mL, and more preferably 30-60 mg:500 mL.

[0032] The present invention also provides a photocatalyst deodorizing spray prepared by the method for preparing the photocatalyst deodorizing spray using the gold-loaded photocatalyst.

[0033] The invention also provides application of the photocatalyst deodorizing spray in deodorizing superfine fiber artificial leather.

[0034] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0035] In the embodiments and comparative examples, the ultrafine titanium dioxide powder is P25 ultrafine titanium dioxide powder; freeze drying is performed in a freeze dryer at a temperature of -40 to -10°C.

[0036] Example 1

[0037] 30 mg of ultrafine titanium dioxide powder was dissolved in 100 mL of deionized water by ultrasonic treatment at a power of 180 W, and then 0.6 mL of tetrachloroauric acid trihydrate aqueous solution (the concentration of tetrachloroauric acid trihydrate in the aqueous solution was 1 mg / mL) and 20 mL of ethylenediamine were added, and the mixture was stirred at a speed of 300 rpm in a dark environment to obtain a mixed solution. The mixed solution was subjected to photodeposition under an LED light with a wavelength of 365 nm and a power of 1 mW, the temperature of the photodeposition was 25 ° C, and the photodeposition time was 5 h; the obtained photodeposition product was freeze-dried for 1 h to obtain a gold-loaded photocatalyst (P25-Au), which was stored in a dark environment.

[0038] 20 mg of gold-loaded photocatalyst was dissolved in 500 mL of ethanol solution (the volume ratio of anhydrous ethanol to deionized water was 1:4), and stirred evenly at a speed of 300 rpm to obtain a photocatalyst deodorizing spray for deodorizing artificial leather.

[0039] Example 2

[0040] 20 mg of ultrafine titanium dioxide powder was dissolved in 100 mL of deionized water by ultrasonic treatment at a power of 180 W, and then 0.6 mL of aqueous solution of tetrachloroauric acid trihydrate (the concentration of tetrachloroauric acid trihydrate in the aqueous solution was 1 mg / mL) and 12.4 mL of triethanolamine were added, and stirred at a speed of 300 rpm in a dark environment to obtain a mixed solution. The mixed solution was subjected to photodeposition under an LED light with a wavelength of 365 nm and a power of 1 mW, the temperature of the photodeposition was 22 ° C, and the photodeposition time was 6 h; the obtained photodeposition product was freeze-dried for 1 h to obtain a gold-loaded photocatalyst (P25-Au), which was stored in a dark environment.

[0041] 30 mg of gold-loaded photocatalyst was dissolved in 500 mL of ethanol solution (the volume ratio of anhydrous ethanol to deionized water was 1:6), and stirred evenly at a speed of 300 rpm to obtain a photocatalyst deodorizing spray for deodorizing artificial leather.

[0042] Example 3

[0043] 50 mg of ultrafine titanium dioxide powder was dissolved in 100 mL of deionized water by ultrasonic treatment at a power of 180 W, and then 0.5 mL of aqueous solution of tetrachloroauric acid trihydrate (the concentration of tetrachloroauric acid trihydrate in the aqueous solution was 1 mg / mL) and 27.5 mL of methanol were added, and stirred evenly at a speed of 300 rpm in the dark to obtain a mixed solution. The mixed solution was photodeposited under a xenon lamp with a wavelength of 380 nm and a power of 300 W, the temperature of the photodeposition was 28 ° C, and the photodeposition time was 4 h; the obtained photodeposition product was freeze-dried for 1.5 h to obtain a gold-loaded photocatalyst (P25-Au), which was stored in a dark and dry place.

[0044] 15 mg of gold-loaded photocatalyst was dissolved in 500 mL of ethanol solution (the volume ratio of anhydrous ethanol to deionized water was 1:3), and stirred evenly at a speed of 300 rpm to obtain a photocatalyst deodorizing spray for deodorizing artificial leather.

[0045] Comparative Example 1 Dissolve 20 mg of ultrafine titanium dioxide powder in 500 mL of ethanol solution (the volume ratio of anhydrous ethanol to deionized water is 1:4), stir evenly, and obtain a photocatalyst deodorizing spray for deodorizing artificial leather.

[0046] Comparative Example 2 10 mg of ultrafine titanium dioxide powder was ultrasonically dissolved in 100 mL of deionized water, and then 0.3 mL of tetrachloroauric acid trihydrate (AuCl3·HCl·3H2O) aqueous solution (in the aqueous solution, the concentration of tetrachloroauric acid trihydrate was 1 mg / mL) and 20 mL of methanol were added, and stirred evenly in the dark to obtain a mixed solution. The mixed solution was photodeposited under a 300 W xenon lamp, the temperature of the photodeposition was 25 ° C, and the time of the photodeposition was 5 h; the obtained photodeposition product was freeze-dried for 1 h to obtain a gold-loaded photocatalyst, which was stored in a dark and dry place.

[0047] 10 mg of gold-loaded photocatalyst was dissolved in 500 mL of ethanol solution (the volume ratio of anhydrous ethanol to deionized water was 1:4), and stirred evenly to obtain a photocatalyst deodorizing spray for deodorizing artificial leather.

[0048] The deodorizing effect of Comparative Example 2 is worse than that of Example 1. This is because Comparative Example 2 uses a high-power xenon lamp for light-loaded synthesis, which causes the loaded gold nano-ions to form particles, reducing the activity of gold and thus reducing the deodorizing effect.

[0049] The performance of the gold-supported photocatalyst of Example 1 and the pure P25 ultrafine titanium dioxide powder of Comparative Example 1 were tested.

[0050] The X-ray diffraction patterns of the gold-supported photocatalyst (P25-Au) of Example 1 and the pure P25 ultrafine titanium dioxide powder of Comparative Example 1 are as follows: Figure 1 As shown. Figure 1 It can be seen that the main components of the pure P25 of Comparative Example 1 and the Au-loaded P25 composite material (gold-loaded photocatalyst) prepared in Example 1 are both P25, and there is no obvious Au signal. The reasons are mainly two aspects. First, the loading amount of Au is very small, which is also a consideration for cost saving; second, the Au in the material is loaded on the surface of P25 in the form of clusters and single atoms, and the catalytic activity of clusters and single atoms is also better.

[0051] The energy spectrum analysis and element mapping results of the gold-loaded photocatalyst of Example 1 and the pure P25 ultrafine titanium dioxide powder of Comparative Example 1 are as follows: Figure 2 As shown, a is the energy spectrum analysis, b is the O element, c is the Ti element, and d is the Au element; the energy spectrum analysis and element mapping results of the gold-loaded photocatalyst of Example 1 both indicate the presence of Au, which is well dispersed on the entire surface of P25 in the form of clusters and single atoms.

[0052] The UV-visible absorption spectra of the gold-supported photocatalyst (Au-P25) of Example 1 and the pure P25 ultrafine titanium dioxide powder of Comparative Example 1 are shown in FIG. Figure 3 As shown by Figure 3 It can be seen that after loading Au, the visible light absorption of the catalyst is significantly improved, and a new peak appears at around 570nm, which is also a sign that Au loading successfully produces surface plasmon resonance (LSPR). The LSPR effect can not only improve visible light absorption, but also generate hot electrons under light, further promoting the photocatalytic reaction.

[0053] The artificial leather sprayed with the photocatalyst deodorizing spray of Example 1 and the artificial leather not sprayed with any catalyst were tested for photocatalyst deodorizing performance. There were at least three appraisers. If the scoring results of the same experiment by the appraisers differed by more than two grades, at least five appraisers were required to repeat the test. If it is uncertain, the middle score can be taken, such as: 3.5. The final result is the arithmetic mean. The judging criteria are: Level 1: no odor; Level 2: there is an odor, but it is not disturbing; Level 3: there is a distinct odor, but it is not disturbing; Level 4: there is a disturbing odor; Level 5: there is a strong disturbing odor; Level 6: there is an unbearable odor.

[0054] The preparation process of the ultrafine fiber synthetic leather (artificial leather) used in experiments 1, 2 and 3 is as follows: 1) using polyester ultrafine staple fibers with a single filament fineness of 0.2dtex as raw materials for laying a net to form a polyester ultrafine staple fiber layer; 2) double-sided reinforcement and needle punching of the polyester ultrafine staple fiber layer, the speed is 2.2m / min, the frequency is 700 times / min, and the double-sided reinforcement uses a mesh made of 3000 twists, 90D / 48F high-strength FDY filaments; 3) ironing, the speed is 3.5m / min, the temperature is 140℃, to form a grey cloth; 4) entering the impregnation tank for pre-shrinking, the water temperature is 95℃, and the time is 8min; 5) drying after impregnation with water-soluble resin, the viscosity of the water-soluble resin is 0cps, the solid content is 18%, and the amount of liquid on the grey cloth is 100%; the drying temperature is 130℃, the speed is 6m / min; 6) Drying after impregnation with water-based polyurethane, the viscosity of the water-based polyurethane is 600cps, the solid content is 45%, and the liquid content of the grey cloth is 160%; drying is carried out in a three-section oven, the temperatures of the three sections are 118℃, 150℃, and 125℃ in sequence, and the speed is 4m / min; 7) Fiber opening: Fiber opening is carried out using NaOH with a concentration of 20g / L, the temperature is 100℃, and the time is 60min; 8) Water grinding: First use two sand rollers for the first water grinding, The mesh number of the two sand rollers is the same, both of which are 220 mesh; another sand roller is used for the second water grinding, with a mesh number of 350 mesh; finally, another sand roller is used for the third water grinding, with a mesh number of 500 mesh; the water grinding speed is 8m / min, and the speed of all sand rollers is 1800 rpm; 9) Rubbing: After being soaked in water, it enters the drum, the steam in the drum is 102℃, and the drum repeatedly swings between 120℃ in the forward direction and 120℃ in the reverse direction, and the drum completes the entire forward to reverse direction within 30s. Or reverse to forward swing angle action; 10) Dyeing: Use disperse dyes for dyeing, and adopt low bath ratio one bath method, the bath ratio is 1:9, the temperature is 122℃; 11) Sanding: First use two sandpaper rollers with a mesh number of 280 for the first sanding, and then use two sandpaper rollers with a mesh number of 500 for the second sanding; finally, use a brush roller for brushing; the sanding speed is 6m / min, and the rotation speed of all sandpaper rollers is 1800 rpm to obtain ultrafine fiber synthetic leather.

[0055] Experiment 1 (artificial leather without catalyst spraying and light exposure): Cut a 14cm×14cm piece of microfiber synthetic leather and put it into a 1L sealed bottle specially used for odor evaluation experiments of automotive parts materials. Heat it to 80℃ and keep it for 2h. After taking out the sample, cool it back to 60℃ and conduct standard identification using the nose-inhaling method. The identification was conducted by three identification personnel, and the identification results were 5, 4, and 5, respectively, with an arithmetic mean of 4.7.

[0056] Experiment 2 (artificial leather without catalyst spraying, exposed to light): Cut a 14cm×14cm piece of microfiber synthetic leather, put it into a 1L sealed bottle specially used for odor evaluation experiments of automotive parts materials, heat it to 80℃, keep it for 2h, put the bottle under a 300W xenon lamp for 1h, then heat the sealed bottle to 60℃, and use the standard air-into-nose method for standard identification by three identification personnel. The identification results were 4, 4, and 4, respectively, and the arithmetic mean was 4.0.

[0057] Experiment 3 (artificial leather sprayed with the photocatalyst deodorizing spray of Example 1): Cut a 14cm×14cm piece of ultrafine fiber synthetic leather, spray the middle part with the photocatalyst deodorizing spray of Example 1, spray 10 times, spray 5mL in total until the leather is moistened, put it into a sealed bottle with a volume of 1L specially used for odor evaluation experiments of automotive parts materials, heat it to 80℃, keep it for 2h, put the bottle under a 300W xenon lamp for 1h, then heat the sealed bottle to 60℃, and conduct standard identification with the nose method, which was conducted by three identification personnel. The identification results were 2.5, 2.5, and 3.5, respectively, and the arithmetic mean was 2.8.

[0058] It can be seen from the odor experiment of artificial leather that the odor of artificial leather sprayed with the photocatalyst deodorizing spray of Example 1 is significantly reduced.

[0059] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a gold-supported photocatalyst, characterized in that: The following steps are included: 1) Ultrasonic mixing of ultrafine titanium dioxide powder and water to obtain a titanium dioxide solution; 2) Mixing titanium dioxide solution, tetrachloroauric acid trihydrate and a sacrificial agent, sequentially performing photodeposition and freeze drying to obtain a gold-loaded photocatalyst.

2. The method for preparing a gold-supported photocatalyst according to claim 1, characterized in that: Step 1) The mass volume ratio of the ultrafine titanium dioxide powder and water is 10-100 mg:100 mL.

3. The method for preparing a gold-supported photocatalyst according to claim 1 or 2, characterized in that: The mass ratio of the tetrachloroauric acid trihydrate in step 2) to the ultrafine titanium dioxide powder in step 1) is 1-5:

100.

4. The method for preparing a gold-supported photocatalyst according to claim 3, characterized in that: The sacrificial agent in step 2) comprises methanol, ethanol, triethanolamine or ethylenediamine; the volume mass ratio of the sacrificial agent to the ultrafine titanium dioxide powder in step 1) is 0.5-0.75 mL: 1 mg.

5. The method for preparing the gold-supported photocatalyst according to claim 4, characterized in that: Step 2) The temperature of the photodeposition is 20-30° C., and the time of the photodeposition is 3-6 hours; the wavelength of the light source used for the photodeposition is 350-380 nm, and the power is 0.8 mW-310 W.

6. The gold-loaded photocatalyst prepared by the method for preparing the gold-loaded photocatalyst according to any one of claims 1 to 5.

7. The method for preparing a photocatalyst deodorizing spray using the gold-supported photocatalyst according to claim 6, characterized in that: The following steps are included: The gold-loaded photocatalyst is dissolved in an ethanol solution to obtain a photocatalyst deodorizing spray.

8. The method for preparing a photocatalyst deodorizing spray using the gold-supported photocatalyst according to claim 7, characterized in that: In the ethanol solution, the volume ratio of anhydrous ethanol to water is 1-9:1-9; the mass volume ratio of the gold-loaded photocatalyst to the ethanol solution is 10-100 mg:500 mL.

9. The photocatalyst deodorizing spray prepared by the method for preparing the photocatalyst deodorizing spray using the gold-supported photocatalyst according to claim 7 or 8.

10. Use of the photocatalyst deodorizing spray according to claim 9 in deodorizing microfiber artificial leather.

Citation Information

Patent Citations

  • Leather nursing liquid for eliminating formaldehyde pollution and peculiar smell, and preparing method thereof

    CN101016573A

  • Leather deodorant

    CN107583452A

  • Spray for eliminating pollutants in air

    CN109745856A

  • Method for preparing titanium dioxide-loaded gold catalyst through photodeposition and application of gold catalyst

    CN111974387A

  • Method for optimizing silver-loaded titanium dioxide photocatalyst efficient disinfectant by response surface method

    CN116173945A